Proceedings of the Third CIPS-SIGHAN Joint Conference on Chinese Language Processing 2014
DOI: 10.3115/v1/w14-6806
|View full text |Cite
|
Sign up to set email alerts
|

Ch2R: A Chinese Chatter Robot for Online Shopping Guide

Abstract: In this paper we present a conversational dialogue system, Ch2R (Chinese Chatter Robot) for online shopping guide, which allows users to inquire about information of mobile phone in Chinese. The purpose of this paper is to describe our development effort in terms of the underlying human language technologies (HLTs) as well as other system issues. We focus on a mixed-initiative conversation mechanism for interactive shopping guide combining initiative guiding and question understanding. We also present some eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…More longitudinal studies about MLU of Mandarin-speaking children should be conducted to explore the relationship between MLU and age. In terms of cross-sectional research, Huang and colleagues (2016) found significant differences between the 3-year-old and 4-year-old groups, and the MLU-w values of the typically developing 3- and 4-year-old children were 3.99 and 4.29, respectively. For children with a language delay, the MLU-w scores of the 3- and 4-year-old children were 3.33 and 3.85, respectively.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…More longitudinal studies about MLU of Mandarin-speaking children should be conducted to explore the relationship between MLU and age. In terms of cross-sectional research, Huang and colleagues (2016) found significant differences between the 3-year-old and 4-year-old groups, and the MLU-w values of the typically developing 3- and 4-year-old children were 3.99 and 4.29, respectively. For children with a language delay, the MLU-w scores of the 3- and 4-year-old children were 3.33 and 3.85, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have shown that MLU was a valuable measure for different languages and different age groups under different sampling procedures (Hewitt et al, 2005; Huang, et. al., 2016; Rice et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations